A mixed behavioural and data-driven method for assessing the shift potential to electric micromobility: evidence from Rome - Nigro, Marialisa; Comi, Antonio; De Vincentis, Rosita; Castiglione, Marisdea (Frontiers in Future Transportation, 2024)
Electric micromobility, both as a private option and as a shared service, can represent an alternative to cars, particularly for given user groups (market segments) and specific classes of travel distance. The paper explores the shifting potential from cars to electric micromobility (specifically, e-bikes and escooters) for commuting trips, which are investigated through floating car data (FCD). The methodology combines the calibration of random utility models (RUMs) and the subsequent simulation through the adoption of FCD spanning the entire city of Rome (Italy). The data used for the calibration of RUM models has been sourced from an on-line revealed preferences and stated preferences survey carried out between November 2020 and January 2021. Socio-economic factors, along with transport features (travel time, access time, monetary costs, perceived safety levels) come into the definition of the mode choice probability. First results showed that in Rome the potential demand for electric micromobility could range between 14% of the FCD sample in the best case (low cost, high accessibility and road infrastructures with high perceived level of safety) to about 2% in the worst case (high cost, low accessibility and low perceived level of safety).